2021
DOI: 10.1186/s12052-021-00151-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to teaching evolution in higher education

Abstract: Background Although progress has been made in evolution education, many educators face significant barriers in their efforts to teach evolution specifically, and science in general. The purpose of this study was to identify faculty-perceived barriers to teaching evolution, specifically in religiously affiliated institutions or institutions with a highly religious student body, as well as resources faculty feel would help promote discourse around faith, evolution and science. To do this, we held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…z 2017 r., poz. 356) or the US (Tolman et al, 2021), or along with non-scientific hypotheses such as creationism (Williams, 2008;Plutzer et al, 2020). In other countries, teachers feel that their pupils have a poor understanding of evolution (Hermann, 2013).…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…z 2017 r., poz. 356) or the US (Tolman et al, 2021), or along with non-scientific hypotheses such as creationism (Williams, 2008;Plutzer et al, 2020). In other countries, teachers feel that their pupils have a poor understanding of evolution (Hermann, 2013).…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…Students join the higher education system with numerous preconceived opinions, which can become big obstacles in improving evolution acceptability. Their religious beliefs, as well as the beliefs of their parents, have a significant impact on their perceptions coupled with inadequate or imprecise information they acquire in secondary school (Tolman et al, 2021). According to a study headed by Miller et al (2006), the evolutionary acceptance of the populace varies significantly among countries and social groups.…”
Section: Frameworkmentioning
confidence: 99%
“…It leads to inadequate responses from a scientific point of view (Tidon & Lewontin, 2004;Andrews et al, 2012). Many of them reinforce common errors such as linearity in evolution, the search for perfection or adaptation as a response to necessity, or even affect the understanding of other areas of biology, such as ecology (Tolman et al, 2021). Despite this, there are few efforts to ensure that students at these levels, high school and first semesters of undergraduate, receive evolution courses, even though it has been shown that in the cases in which this is done, the understanding of biological phenomena becomes simpler (Jördens et al, 2016) as a consequence of having greater clarity in the basic theory of the discipline.…”
Section: Introductionmentioning
confidence: 99%